2008
DOI: 10.1377/hlthaff.27.2.393
|View full text |Cite
|
Sign up to set email alerts
|

New Evidence Regarding Racial And Ethnic Disparities In Mental Health: Policy Implications

Abstract: Minorities have, in general, equal or better mental health than white Ameri-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
301
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 587 publications
(338 citation statements)
references
References 41 publications
(28 reference statements)
16
301
1
Order By: Relevance
“…Moreover, other research has demonstrated that in the general population these ethnic minority groups have lower rates of mental health disorders than White non-Hispanics 32 . Thus, some of the processes at work in our study population are likely to be operative in non-diabetic ethnic populations, e.g., nondiabetes-specific risk and protective factors are associated with non-diabetes-specific psychological outcomes among people with diabetes.…”
Section: Discussion Ethnicitymentioning
confidence: 96%
“…Moreover, other research has demonstrated that in the general population these ethnic minority groups have lower rates of mental health disorders than White non-Hispanics 32 . Thus, some of the processes at work in our study population are likely to be operative in non-diabetic ethnic populations, e.g., nondiabetes-specific risk and protective factors are associated with non-diabetes-specific psychological outcomes among people with diabetes.…”
Section: Discussion Ethnicitymentioning
confidence: 96%
“…Eunice C. Wong, Rebecca L. Collins, Jennifer L. Cerully, Rachana Seelam, Elizabeth Roth R acial and ethnic minorities are significantly more likely than whites to delay or forego needed mental health care, and, if they do seek treatment, they are more likely than whites to drop out (McGuire and Miranda, 2008). Mental illness stigma and discrimination are thought to contribute to these racial/ethnic disparities in service utilization (U.S. Department of Health and Human Services, 2001).…”
Section: Racial and Ethnic Differences In Mental Illness Stigma And Dmentioning
confidence: 99%
“…Disparities in minority groups' utilization and experiences of mental health services as well as patient-provider relationships are welldocumented (Alegria et al, 2008;DHHS, 2001;McGuire & Miranda, 2008). These inequalities have been attributed to provider's lack of empathy, cultural competence, provider's racial bias, as well as patients' distrust in the health care system (Constantine, 2007;Cooper et al, 2012;DHHS, 2001; L. Thompson & McCabe, 2012).…”
Section: Introductionmentioning
confidence: 99%